Does Taobao increase the popularity of counterfeit purchasing in China? - Yang, Mengyao (2016)
Both The Office of the United States Trade (USTR) and the European Commission reported that the total number of seized counterfeit products from China significantly surpass those from other countries (Yang, 2016). With the development of technology especially the popularity of Internet in China, Chinese young consumers who is skilful in using online shopping prefer to purchase counterfeits online and thereby solving counterfeiting issues in China seems more difficult than ever.